Depression as an independent risk factor for cardiovascular diseases and cognitive impairment in people aged 25-44 years - V. V. Gafarov; A. V. Sukhanov; E. A. Gromova; I. V. Gagulin; A. V. Gafarova (Кардиоваскулярная терапия и профилактика)
Aim. To establish associations between the depression level as an independent cardiovascular risk factor and cognitive impairment (patterns of memory, attention and thinking) in people aged 25-44 years.Material and methods. In 2013-2016, a random representative sample of people aged 25-44 years was studied in one of the Novosibirsk districts. A total of 463 men (mean age 35,94±5,96 years) and 546 women (mean age 36,17±5,99 years) were examined. Standardized tests were used to assess cognitive function. Depression level was assessed according to the MOPSY (MONICA-psychosocial) World Health Organization program criteria.Results. In the surveyed random representative sample of people aged 25-44 years, the prevalence of higher education was the highest (60,5%). The depression prevalence in women was higher than in men: high depression level — 15,84 and 8,64%; the mean depression level was 25,71 and 21,3%, respectively. Univariate analysis showed that the attention stability according to the dot cancellation test at a moderate and high depression level was reduced only in men with higher education, compared with those without depression (p=0,018). In persons of both sexes with secondary professional education in a random representative sample of persons aged 25-44 years, associations between depression and memory pattern disturbances were identified. In the resulting multivariate model, men in a random representative sample of persons aged 25-44 years without depression did not have any cognitive impairment in patterns of memory, attention and thinking.Conclusion. An association has been established between the depression and cognitive impairment (patterns of memory, attention and thinking) in people aged 25-44 years.